2009
DOI: 10.1086/606046
|View full text |Cite
|
Sign up to set email alerts
|

The Immunogenicity of 7‐Valent Pneumococcal Conjugate Vaccine versus 23‐Valent Polysaccharide Vaccine in Adults Aged 50–80 Years

Abstract: http://www.clinicaltrials.gov/NCT00197821.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

5
63
1
3

Year Published

2010
2010
2023
2023

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 138 publications
(72 citation statements)
references
References 23 publications
5
63
1
3
Order By: Relevance
“…We were also able to compare the natural levels of functional antibodies to functional antibodies measured following the administration of conjugate or polysaccharide vaccines in infants and adults, respectively, in the United Kingdom (16,17).…”
mentioning
confidence: 99%
“…We were also able to compare the natural levels of functional antibodies to functional antibodies measured following the administration of conjugate or polysaccharide vaccines in infants and adults, respectively, in the United Kingdom (16,17).…”
mentioning
confidence: 99%
“…Although several smaller earlier studies did not show that priming with pneumococcal conjugate vaccine followed by polysaccharide vaccine enhanced immunogenicity, more recent larger studies showed improved response (72)(73)(74). These larger studies using PCV13 conjugate vaccine followed a year later by the polysaccharide-based PPSV23 resulted in higher antibody activities after a month of PPSV23 administration, but at 6 months the antibody levels in booster recipients fall to baseline (66,75).…”
Section: Focused Reviewsmentioning
confidence: 92%
“…9 Some immunological studies 10 have suggested improved immunogenicity of PCV7 over PPV23 in adults and/or the elderly. [11][12][13][14][15] while others have reported no significant differences. 10,[16][17][18][19] In 2014 the first large clinical trial of PCV13 in the adults aged >65 y (CAPiTA trial -Community Acquired Pneumonia Immunization Trial in Adults 20 ) was completed.…”
Section: Introductionmentioning
confidence: 93%